Analysis of Risk Factors for Pulmonary Tuberculosis in Cirascas District, East Jakarta, 2022 - Sopiani, Pina; Maemun, Siti; Azijah, Izzatul; Pratiwi, Tiara Zakiyah; Saputra, Rahmat (The Indonesian Journal of Infectious Diseases, 2025)
Background: Tuberculosis (TB) is a global public health problem, with Indonesia ranked second in the world in 2022. In East Jakarta, TB cases continue to increase, including in the Ciracas sub-district. This study aims to identify risk factors for pulmonary TB cases in the Ciracas sub-district in 2022. Methods: The method of this study was quantitative with a case-control design, involving 115 samples (23 cases and 92 controls) selected by purposive sampling technique. Results: The results showed that there was a relationship between contact history and TB patients (p=0.004; OR=6.27; 95% CI=1.86 – 21.11) and occupancy density (p=0.000; OR=29.52; 95%CI: 8.99 – 96.89) with Pulmonary TB infection. However, there was no significant relationship between gender, age, education, occupation, marital status, family income, and knowledge of patients with Pulmonary TB infection. Conclusion: In conclusion, contact with TB patients and housing density increases the risk of pulmonary TB infection. Therefore, it is recommended that isolation of TB patients to a place from the surrounding environment needs to be done to prevent transmission and airborne contamination